2021
DOI: 10.2196/23306
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Innovation Capabilities of Health Care Organizations on the Quality of Health Information Technology: Model Development With Cross-sectional Data

Abstract: Background Large health organizations often struggle to build complex health information technology (HIT) solutions and are faced with ever-growing pressure to continuously innovate their information systems. Limited research has been conducted that explores the relationship between organizations’ innovative capabilities and HIT quality in the sense of achieving high-quality support for patient care processes. Objective The aim of this study is to expla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 83 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…In addition, a look at the outcomes of the analysis network process revealed that the three factors of “lack of top-executive supports”, “unstable organizational environment’, and “lack of professional skills of the project team” had the most importance, respectively, and should be specifically considered in implementation of clinical information technology projects. Edsar et al considered the top management team, information technology department, and organization at large as significant factors in this regard [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a look at the outcomes of the analysis network process revealed that the three factors of “lack of top-executive supports”, “unstable organizational environment’, and “lack of professional skills of the project team” had the most importance, respectively, and should be specifically considered in implementation of clinical information technology projects. Edsar et al considered the top management team, information technology department, and organization at large as significant factors in this regard [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the second step, five maturity models (CHECK-IT [9], EMRAM [10], WCS [11], KIT-CON [12], and MOST WIRED [13]) as well as the KHZG's eligibility criteria were reviewed for maturity objects (MOs). They are criteria for assessing digital maturity (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…This could also signal that leadership and health care administrators could be more likely to test varying systems and approaches to care [40]. These leaders may thus have a more positive perception of the advantages of using health information technology to improve efficiency and provide high-quality and safer treatment services to patients [41].…”
Section: Internal and External Organizational Factors Associated With...mentioning
confidence: 99%